ANALYSIS OF TRENDS IN IMPROVING THE INVESTMENT CLIMATE IN UZBEKISTAN AND METHODS FOR MINIMIZING RISKS - Isomitdinova Gulbaxor Kurbonaliyevna (Modern American Journals, 2025)
In this study, we will consider the current state of the investment climate in the economy of Uzbekistan, as well as methods and tools aimed at reducing the risks associated with investment projects. The paper will analyze the theoretical and practical aspects of risk management, which play a key role in stimulating investment activity and attracting foreign investment. Special attention will be paid to the stages of identification, assessment, control and minimization of risks necessary for the successful implementation of investment projects. The article will present various definitions of risk proposed by economists, as well as methods of qualitative and quantitative risk analysis. In addition, we will consider modern approaches to risk management. Effective tools such as diversification, guarantees, insurance, and financial protection measures for project risks will be offered to minimize risks.
Keywords: Investment climate, risk minimization, risk management, investment projects, foreign investments, qualitative and quantitative assessment, project risks, sources of financing, investment activity, expert assessment.